Enriching UML statecharts through a metamodel : a model-driven approach for the graphical definition of DEVS atomic models - Dalmasso, Fidel; Blas, María Julia; Gonnet, Silvio (IEEE Latin America Transactions, 2023)
The Discrete Event System Specification (DEVS) formalism provides a set of mathematical elements for modeling time-varying systems. However, when DEVS models are implemented in an executable representation (i.e., using a generalpurpose programming language), some deviation from the formalism is unavoidable. One way to bridge the gap between modeling and simulation theory and practice is to define new artifacts that support both views during the specification. When the specification is supported with a graphical representation, the formalization task is less complex and can be performed by nonexpert modelers. For DEVS atomic models, most common graphical representation is through UML statecharts. In this paper, we present a theoretical and practical metamodel for the definition of atomic models structured following the Classic DEVS with Ports formalization. Such a metamodel is the core of a model-driven approach used to develop a modeling software tool that employs enriched UML statecharts for the graphical representation of the DEVS behavior. In here, the traditional UML statechart representation is enriched with a set of new components with the aim to provide a broad definition of DEVS atomic models. The final software tool is deployed as a plugin for Eclipse Platform.
Keywords: Discrete event system specification; Modeling and simulation; Theory and practice; State diagram